Bouveret syndrome as a rare cause of gastric outlet obstruction. Issue 2 (2nd April 2020) - Kudaravalli, Pujitha; Saleem, Sheikh A.; Goodman, Alexandra; Pendela, Venkata Satish; Arif, Muhammad Osman
Abstract: Biliary-enteric fistula is a rare complication of cholelithiasis that can lead to gallstone ileus. Gallstone impaction in the duodenum and pylorus is extremely rare and can lead to gastric outlet obstruction, a condition known as Bouveret syndrome. Bouveret syndrome needs to be diagnosed and managed in a timely fashion, as it has a high mortality rate. We describe a case of an elderly patient who presented with Bouveret syndrome secondary to impaction of the biliary calculus in the first part of duodenum.